2022
DOI: 10.1021/acs.jpclett.2c00403
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Controlled Fabrication of Surface-Enhanced Raman Scattering Hot Spots through Photoinduced Dewetting of Silver Thin Films

Abstract: A well-designed narrow gap between noble metal nanostructures plays a prominent role in surface-enhanced Raman scattering (SERS) to concentrate electromagnetic fields at the local point, called a "hot spot". However, SERS-active substrate fabrication remains a substantial hurdle due to the high process cost and the difficulty of engineering efficient plasmonic hot spots at the target area. In this study, we demonstrate a simple photolithographic method for generating ultrasensitive SERS hot spots at desired po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The development of a 3D structure on a substrate through self-assembly processes is an effective strategy to generate “hotspots” and improve the SERS sensitivity. , Self-assembled plasmonic nanostructures were prepared commonly through either electron-beam lithography or photolithography techniques, nanoimprint lithography, or conventional colloidal self-assembly process . However, these methods present a significant challenge and are costly .…”
Section: Introductionmentioning
confidence: 99%
“…The development of a 3D structure on a substrate through self-assembly processes is an effective strategy to generate “hotspots” and improve the SERS sensitivity. , Self-assembled plasmonic nanostructures were prepared commonly through either electron-beam lithography or photolithography techniques, nanoimprint lithography, or conventional colloidal self-assembly process . However, these methods present a significant challenge and are costly .…”
Section: Introductionmentioning
confidence: 99%
“…However, on silica substrates modified with hydrophobic silane self-assembled monolayers, the surface hydrophobicity leads to a slip boundary condition at the substrate; the liquid film was observed to undergo nucleated dewetting as opposed to the spinodal dewetting that usually occurs on a hydrophilic substrate. Unfortunately, as the mechanical perturbations from the tip of AFM are not negligible for low-viscosity liquids, AFM experiments have been mainly employed to image high-viscosity liquids, such as polymers, molten solids and metal thin films to understand their interfacial instability dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Also, La and co-workers, have recently demonstrated that the SERS substrate based on nanoporous Au alloys showed a SERS EF up to 10-times greater than that of the monolayer Au NPs and exhibited superior sensitivity down to 1 fM concentrations of analyte molecules. Such nanoporous structures have been prepared through different physical and chemical routes such as chemical synthesis and self-assembly, Langmuir–Blodgett, electron beam lithography, chemical dealloying, electrochemistry, , treatment of oxygen plasma of thermally deposited films, and dewetting of metallic films to create a porous 3D framework. All of these methods are time-consuming and costly and have difficulty in generating 3D plasmonic nanostructures.…”
Section: Introductionmentioning
confidence: 99%